Unveiling the nature of 11 dusty star-forming galaxies at the peak of cosmic star formation history. Issue 1 (8th March 2021) - Pantoni, L; Lapi, A; Massardi, M; Donevski, D; Bressan, A; Silva, L; Pozzi, F; Vignali, C; Talia, M; Cimatti, A; Ronconi, T; Danese, L
ABSTRACT: We present a panchromatic study of 11 (sub-)millimetre selected DSFGs with spectroscopically confirmed redshift (1.5 < z spec < 3) in the GOODS-S field, with the aim of constraining their astrophysical properties (e.g. age, stellar mass, dust, and gas content) and characterizing their role in the context of galaxy evolution. The multiwavelength coverage of GOODS-S, from X-rays to radio band, allow us to model galaxy SED by using cigale z with a novel approach, based on a physical motivated modelling of stellar light attenuation by dust. Median stellar mass (≃ 6.5 × 10 10 M⊙ ) and SFR (≃ 241 M⊙ yr −1 ) are consistent with galaxy main sequence at z ∼ 2. The galaxies are experiencing an intense and dusty burst of star formation (median L IR ≃ 2 × 10 12 L ⊙ ), with a median age of 750 Myr. The high median content of interstellar dust ( M dust ≃ 5 × 10 8 M⊙ ) suggests a rapid enrichment of the ISM (on time-scales ∼10 8 yr). We derived galaxy total and molecular gas content from CO spectroscopy and/or Rayleigh–Jeans dust continuum (10 10 ≲ M gas /M⊙ ≲ 10 11 ), depleted over a typical time-scale τ depl ∼ 200 Myr. X-ray and radio luminosities ( L X = 10 42 –10 44 erg s −1, L $_{1.5\, {\rm GHz}}=10^{30}\!-\!10^{31}$ erg s −1, L $_{6\, {\rm GHz}}=10^{29}\!-\!10^{30}$ erg s −1 ) suggest that most of the galaxies hosts an accreting radio-silent/quiet SMBH. This evidence, along with their compact multiwavelength sizes (median r ALMA ∼ r VLA = 1.8 kpc, rHST = 2.3 kpc) measured from high-resolution imaging ( θ res ≲ 1 arcsec), indicates these objects as the high -z star-forming counterparts of massive quiescent galaxies, as predicted e.g. by the in situ scenario. Four objects show some signatures of a forthcoming/ongoing AGN feedback, which is thought to trigger the morphological transition from star-forming discs to ETGs.